Relasi Agama dan Kekuasaan dalam Pembentukan Hukum Islam di Nusantara Abad XIV-XIX - Moh Nur Fauzi ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2017)
This paper discusses the relationship between culture, religion, and power in the XIV-XIX century associated with the process of formation of Islamic law in Nusantara; the law that grows and develops as a result of dialectical process between the social and cultural reality of the people of Nusantara. This textual and contextual dialectics gives birth to a unique legal system because the archipelagic society is plural and multicultural social system. From this dialectical process, there is an acculturation that give rise to the contextual and progressive dynamics of Islamic law which respect local traditions and wisdom. Furthermore, the involvement of the power authority also contributes to its development. There are two strategies used in the development and establishment of Islamic law in Nusantara, namely cultural strategy and ideological strategy. At this point, Islamic law in Nusantara is experiencing rejuvenation because it always dialogues with the surrounding social reality. Ultimately, the discourse of Islamic law in Nusantara shows its existence as a unique and genuine legal system of Nusantara, in favor of universal human values, and not just the result of fixed Islamic thought and law of the past.